Influence of adopting Amazon Cloud computing services in e-commerce in small and medium organization, Malaysia / Alireza Passari, Leila Radmand and Yasser Batoie - Radmand, Leila; Batoie, Yasser; Passari, Alireza (Faculty of Business Management, 2013)
The main purpose of this study is to examine significant factors such as performance, implementation method, cost and time at popular platforms such as Amazon Cloud server for small and medium businesses that need implementation e-commerce. From of many great Cloud Computing advantages, researcher attempts to find out reliable objectives which are related to real businesses such as performance, implementation method and comparing affect of cost and time in development project management to answer that how businesses can move to cloud computing. It will be conducted by reviewing case study of company who working on e-commerce and have changes from shared hosting to new cloud computing services. To complete the case study methodology, it will be continued by interview of IT managers from selected company to fulfill all information. In conclusion, researcher attempts to give an initial document to research cloud computing for small and medium businesses, and then to examine the futures of those selected platforms to implement could-awareness which can guide businesses as roadmap in electronic commerce sector. The result of this study can enhance performance of making decision of organization who wants to implement or to transform their business to new electronic commerce by using all advantages from cloud computing.